2004
DOI: 10.1007/s00467-004-1496-y
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous cyclophosphamide-resistant systemic lupus erythematosus in Arizona

Abstract: Systemic lupus erythematosus (SLE) tends to be severe and to have a variable response in childhood. We undertook this retrospective study to assess response rates and outcome in 14 children with SLE. Mean age at onset was 12.8+/-3.1 years. Ten patients were female and 4 were male, and 12 patients (86%) were Hispanic. Creatinine clearance prior to therapy was 104+/-36 ml/min. All had hematuria and proteinuria with a protein/creatinine ratio of 3.9+/-4.8. WHO classification of renal biopsies revealed class IV in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
13
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 32 publications
0
13
1
Order By: Relevance
“…Conversely, our CRR rate was more than three times higher than that found among African-American children ( Table 6) by Lau et al 5 But why our CRR rate compares favourably with Chinese children 37 and better than African Americans 5 who share similar racial origin with our patients is unclear. Compared with other studies (21-41%), 8,36,37 our relapse rate (14.3%) was much lower. Our disease activity (28.6%) is similar to that in Egyptian (22.2%), 8 but higher than in Serbian children (7.5%).…”
Section: Discussioncontrasting
confidence: 81%
“…Conversely, our CRR rate was more than three times higher than that found among African-American children ( Table 6) by Lau et al 5 But why our CRR rate compares favourably with Chinese children 37 and better than African Americans 5 who share similar racial origin with our patients is unclear. Compared with other studies (21-41%), 8,36,37 our relapse rate (14.3%) was much lower. Our disease activity (28.6%) is similar to that in Egyptian (22.2%), 8 but higher than in Serbian children (7.5%).…”
Section: Discussioncontrasting
confidence: 81%
“…[2,3,11] Diffuse proliferative lupus glomerulonephritis is the most common and the most severe histologic type of lupus nephritis, occurring in 40-75% of children with SLE. [11][12][13][14][15] In our study, DPLN was also found to occur in 56.5% of all patients, being the most common type of lupus nephritis.…”
Section: Discussionmentioning
confidence: 73%
“…[15,17] The most widely used intravenous cyclophosphamide regimen consists of monthly infusions with 500-1,000 mg/m 2 doses for six months, followed by 2-4 monthly infusions for 18-24 months. [13,[17][18][19][20][21] Compared with daily oral cyclophosphamide (1-3 mg/kg/day), the intravenous route has been accepted to have the advantage of less severe side effects, like cystitis and bladder cancer, as the cumulative doses are smaller. [17] However, not all investigators encounter such difficulties if the daily oral dose of cyclophosphamide does not exceed 1.5 mg/kg/day and daily treatment does not exceed 4-6 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the high prevalence of serious adverse effects has been of concern, particularly in children and adolescents [4,13,[23][24][25][26][27][28][29]. The toxic effects of IV CYC often depend on the Fig.…”
Section: Discussionmentioning
confidence: 99%